RESPONSIVE WEB DESIGN MENGGUNAKAN BOOTSTRAP DALAM MERANCANG LAYOUT ORDERAN MAKANAN - Junellson; Sitohang, Sunarsan (LPPM Universitas Putera Batam, 2024)
Nowadays we use increasingly developing technology. In this technology, we definitely use websites to find all the information we need. Many Indonesians are familiar with the internet and use it in their daily lives. Websites may using for various things like product promotions, study, work and much more. In this research, we will create an order input website using a bootstrap framework for a small food stall business. Because, there are still many stall sellers who still use manual systems in ordering and calculating total orders. This will create the risk of forgetting orders and making mistakes in giving change. The research using the waterfall method. The results of the researches is a food order input website with a responsive display that is used to manage food orders. The goal of this researches are to design a website for inputting food orders for food stall businesses with the hope that we can help sellers to carry out work effectively, quickly and thoroughly in this work.